Advances in Material Forming and Joining 5th International and 26th All India Manufacturing Technology, Design and Research Conference, AIMTDR 2014 - Narayanan, R. Ganesh; Dixit, Uday Shanker (Topics in Mining, Metallurgy and Materials Engineering, 2015)
This edited book contains extended research papers from AIMTDR 2014. This includes recent research work in the fields of friction stir welding, sheet forming, joining and forming, modeling and simulation, efficient prediction strategies, micro-manufacturing, sustainable and green manufacturing issues etc. This will prove useful to students, researchers, and practitioners in the field of materials forming and manufacturing.